The effects of post-hypnotic suggestion on muscular performance: an EMG study on the forearm during a static handgrip endurance test - De Giorgio, Andrea; Vieira, Taian; Buzzachera, Cosme F.; Kuvačić, Goran; dell’Anna, Stefano; Bragazzi, Nicola; Angilletta, Sonia; Alessandria, Marco (Biology of Sport, 2025)
Hypnosis is known for its effects on various psychophysiological phenomena, such as perception, emotions, fatigue, and muscle strength. Besides the conflicting evidence on the influence of hypnosis on muscle performance, its role in influencing central or peripheral fatigue remains poorly understood. Here, we investigated the effects of a single hypnosis session, terminated with a precise posthypnotic suggestion, on muscle strength, endurance, and myoelectric activity. Thirty participants ( M = 17, F = 13) were divided into a Control (CO) and a Hypnosis group (HY). Handgrip strength and endurance were tested in three pre- and post-training phases: i) holding the handgrip as strongly as possible for 5 seconds (i.e. a measure of muscle strength); ii) after a 1-minute passive pause, holding the handgrip as strongly and as long as possible (i.e. a measure of muscle endurance); iii) after a further 1 minute pause, the first trial was repeated. All these procedures were repeated after a 30 minute rest period during which the CO could use the time freely, the HY was subjected to the hypnosis session. During the experimental procedures, surface EMG was applied to the forearm muscles to assess neuromuscular fatigue. Regardless of a stronger improvement between pre- and post-processing in the HY, we found no interaction effect between the groups. This suggests that a single post-hypnotic suggestion is not sufficient to significantly increase the force exerted over time (i.e., impulse), and that the observed HY improvement may be influenced by highly susceptible participants. Furthermore, despite this difference, we found no change in forearm muscle activation. Our results show that a single hypnosis session negligibly altered muscular performance. These findings contribute to the debate on the topic of hypnosis and fatigue but require further investigation, given the observed tendency of the hypnosis group to delay fatigue.